Differences in the use of municipal bonds by rural municipalities across the Polish territory - Hadryjańska, Barbara (Różnice w użyciu obligacji komunalnych przez gminy wiejskie w Polsce, 2019)
The main purpose of this paper was to present the extent of using municipal bonds and to find a statistically significant relationship between the location of a municipality in the macroregion and the use of bonds. The study was carried out in 2017. The basic research tool was a survey questionnaire administered in 606 rural municipalities, and132 surveys were sent back by rural municipalities located across all voivodeships. Approximately 90% of the municipalities surveyed access EU financing, loans and credits while less than 30% issue bonds. This seems to be primarily caused by the municipal authorities’ cautiousness and reluctance to rely on instruments they do not know well. Municipalities located in the north-western and north-eastern macroregions willingly issued bonds. Conversely, municipalities located in the eastern and central macroregions are the least interested in these instruments. A chi-squared-based analysis of correlation was performed
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 7-18